2020
DOI: 10.3390/ijerph17145150
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Number of Noncommunicable Diseases and Health-Related Quality of Life in Chinese Older Adults: A Cross-Sectional Survey

Abstract: China has the largest population of older adults, most of whom suffer from one or more noncommunicable diseases (NCDs). The harm of the number of NCDs on the health-related quality of life (HRQOL) of older adults should be taken seriously. A sample of 5166 adults, aged 60 years and older, was included in this study. The Chinese version of the World Health Organization Quality of Life-Old (WHOQOL-OLD) instrument was used to assess the HRQOL. Multiple linear regression models were established to determine the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
11
0
3
Order By: Relevance
“…The highest dimension score was the intimacy dimension score, which was close to or higher than that obtained in different cultures as well (12,13,16,(19)(20)(21). During the development of WHOQOL-OLD, it is noteworthy that the death and dying dimension score, which is sensitive to different cultures, was lower than most Western cultures but higher than that of Eastern cultures (16,22,23,15). Previous studies have shown that, death is perceived differently in Eastern and Western societies (24).…”
Section: Discussionsupporting
confidence: 58%
“…The highest dimension score was the intimacy dimension score, which was close to or higher than that obtained in different cultures as well (12,13,16,(19)(20)(21). During the development of WHOQOL-OLD, it is noteworthy that the death and dying dimension score, which is sensitive to different cultures, was lower than most Western cultures but higher than that of Eastern cultures (16,22,23,15). Previous studies have shown that, death is perceived differently in Eastern and Western societies (24).…”
Section: Discussionsupporting
confidence: 58%
“…3 The incidence of age-related chronic diseases, such as cardiovascular and cerebrovascular diseases, endocrine and metabolic diseases, digestive system diseases, and chronic lung diseases, is significantly increasing, and the incidence of chronic lung diseases is significantly increasing. 4 A recent epidemiological study in the elderly population in China has demonstrated that up to 75.8% of residents over 60 years old suffer from at least one chronic disease. 5 Multimorbidity is common with depression and chronic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases of the elderly also present the characteristics of high disability rate and multiple diseases. Diseases affect each other, and the group of elderly suffering from two or more chronic diseases is gradually expanding (12)(13)(14). Numerous studies have also shown that the chronic diseases not only bring damage to the physical health of the elderly, but also affect the mental health of elderly patients with chronic diseases (15,16).…”
Section: Introductionmentioning
confidence: 99%